The Dynamics Of Financial Literacy And Accounting Literacy In Coastal Communities - Lia Dwi Martika; Hamzah, Amir; Oktaviani Rita Puspasari (Jurnal Akuntansi, 2024)
This study analyses the factors affecting financial and accounting literacy. The sample in this study was 281 respondents. Quantitative research methods are used to test hypotheses and analyse data using SEM with LISREL software. The results showed that financial attitudes, financial behaviour, locus of control and financial inclusion positively affect financial literacy, and financial attitudes, financial behaviour, locus of control and financial inclusion affect accounting literacy, and financial literacy positively affect accounting literacy.